The boy who ate stars - Yuson, Alfred A.; Parrocha, Beth A. (Mandaluyong, Metro Manila Cacho Pub. House, 1991)
A boy welcomes the advent of machinery to his village which speeds up the cutting down of the forest so he can see the stars. But the villagers soon begin to suffer from the environmental effects of deforestation.
1990 Palanca Award Winner